(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The study of stem cells in regenerative dentistry is the most precious in-progress research. Stem cells are the cells that have the self-renewal capacity and can differentiate to mature cells. Stemcells also have the prospective to form dentin matrix, bone and neuronal cellsrapidly. Stem cell-based therapeutic approaches provide a better and attractive alternative that the classical dental treatments because of their questionable efficacy and durability. The most promising alternative for tooth loss is the utilization of stem cells and induced pluripotent for the regeneration of the whole tooth. Therefore helping with the progress in inducing bone rejuvenation, treating damaged teeth, stem cell-based therapy plays a vital role. So, this article will highlight the role and importance of stem cells in regeneration in Dentistry